2018
DOI: 10.1186/s12939-018-0895-9
|View full text |Cite
|
Sign up to set email alerts
|

Using concept mapping to identify policy options and interventions towards people-centred health care services: a multi stakeholders perspective

Abstract: BackgroundPeople-centred health care (PCC) services are identified by the WHO as important building blocks towards universal health coverage. In 2016 the WHO formulated a comprehensive framework on integrated PCC services based on an international expert consultation. Yet, expert opinions may fail to recognize the needs of all health system stakeholders. Therefore, a consultation method that includes the health workforce and laypersons, can be instrumental to elaborate this framework more in-depth. This resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…Concept mapping has been proposed for use as a structured way to develop a framework for planning and evaluation ( 14 ). It has been used in the field of health systems to develop an integrative framework for delivering people-centered health care services ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Concept mapping has been proposed for use as a structured way to develop a framework for planning and evaluation ( 14 ). It has been used in the field of health systems to develop an integrative framework for delivering people-centered health care services ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…SW contributed to project conception and design, and critically revised the manuscript. AVH provided project supervision, contributed to project The Concept Mapping Process (Adapted from Leyns et al, 2018) [27].…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…To identify what works within the local context, and to promote sustainable improvement in community health, existing needs and resources of individuals with T2D, their families and communities are to be considered [22][23][24][25][26]. This type of healthcare design is known as 'People-Centred Health Care', de ned as 'an approach to care that consciously adopts individuals', carers', families' and communities' perspectives as participants in, and bene ciaries of, trusted health systems that respond to their needs and preferences in humane and holistic ways' [27]. No studies were found that thoroughly explored needs and resources of people living with T2D in Bolivia.…”
Section: Introductionmentioning
confidence: 99%
“…To identify what can work within the local context, and to promote community ownership, engaging individuals with T2D, their families and communities in the design and implementation of prevention and treatment solutions are to be considered [25][26][27][28][29][30]. This type of healthcare design is known as 'People-Centred Health Care', de ned as 'an approach to care that consciously adopts individuals', caregivers', families' and communities' perspectives as participants in, and bene ciaries of, trusted health systems that respond to their needs and preferences in humane and holistic ways' [31]. No studies were found that thoroughly explored the needs and resources of people living with T2D in Bolivia.…”
Section: Introductionmentioning
confidence: 99%